The joy of bioresources: Sustainable forest-recreation connections - Yu-Fai Leung (BioResources, 2013)
Forests have long-standing relationships with humanity beyond the material aspects. Recreation is an essential human need, and forests possess intrinsic values to support such a need in direct, authentic, and emotional ways. Quality recreation experiences can lead to a greater appreciation of bioresources and deeper support for forest conservation. The forest-recreation connections should be celebrated and sustained in this age of rapid social, environmental, and technological changes.